Cerebellar Mutism - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Of a series of 15 children operated for cerebellar tumor at University Hospital Rotterdam-Dijkzigt, The Netherlands, 5 developed "cerebellar mutism" and subsequent dysarthria after surgery, and 2 had mild speech problems.